Europe’s security threats: Ukraine revisited - Balla, Evanthia (2017)
More than a year after the Minsk II agreement was signed, in February 2015, it is all too apparent that the Ukraine crisis is far from over, while Europe becomes more and more unstable. Today Europe faces a plethora of security threats, different in nature, cause and treatment, such as the on-goingeconomic crisis, the AraSpring and the war in Syria, the rise of the Islamic State and the terrorist attacks in the heart of Europe, the refugee crisis and the aggressive policy of Russia in Ukraine and beyond. In the particular case of Ukraine, the Union’s failure to conclude a landmark Association Agreement with the country in 2013 and its incapacity toavert Russia’s aggressive policies and actions in the region afterwards – as was Russia’s annexation of Crimea and Sevastopol the current clashesin the east of the country – raised serious questions. about EU’s global as well as regional power. Is the European Union ready to play a pivotal role in its neighbourhood and in the world? What are the lessons that Europe must draw from the Ukraine conflict in order to achieve a comprehensive, efficient and credible external policy?